As competências matemáticas no mercado de trabalho brasileiro: O papel da escolaridade e implicaç\~oes para os rendimentos - Maurício Cortez Reis (Instituto de Pesquisa Econômica Aplicada (IPEA), 2025)
– In many occupations, having mathematical skills is considered a necessary condition for workers to perform adequately. For the high proportion of low-skilled workers in Brazil, this condition may constitute a barrier to access better jobs and undermine their performance in the labor market. This paper aims to analyze how the importance attached to mathematical skills or the ability to work with numbers is related to labor earnings, and how schooling can influence this process. The results indicate that occupations that are more closely related to mathematics usually offer higher salaries, and that a higher level of education seems not only to facilitate access to this type of occupation, but also to contribute to greater earnings differential relative to less schooled workers when compared to occupations that do not value these same skills.
Keywords: I26; J24; J31; 330; Mathematics; occupation; schooling; labor earnings